(untitled) (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article presents theoretical analyze the importance of implementation the concept of inclusive design in urban space; the relevance between the implementation of inclusive design and the quality of life of citizens of the settlement. Inclusive design is design that considers the full range of human diversity with respect to ability, language, culture, gender, age and other forms of human difference. Increasing the number of elderly people (9,4 mln people over 60 or 22% of the population of Ukraine), people with disabilities (2,6 mln people – 6% of the population), families with young children, pregnant (4 % of the population) makes to the city, its design and infrastructure new challenges. These groups risk becoming effectively excluded from significant parts of city life, suffering marginalisation, exclusion and isolation. Limiting a city’s access to just a part of the population while ignoring a significant other part, is economically, socially and politically unsustainable. Inclusive design at the city create the opportunity to guarantee equal access to fundamental rights; improve the quality of life of its population and ensure that everybody - regardless of age, mobility or ability - has equal access to all the resources and pleasures cities have to offer. Inclusive design creates an opportunity to support and create equal living conditions for the most vulnerable groups (people with disabilities, the elderly, families with young children). Implementation the ID to the urban space also support development economical sustainability of the city: increase the level of employment people and reducing unemployment, accordingly increasing the purchasing power of citizens, local business development, increase income to the budget; reduction the level of social exclusion, isolation and therefore increase the degree of independence of the client and the reduction of funds for social welfare and individual support. Creation access to the education facilities will increase the level of education. As the results, better education support better employment and higher salary. Creation accessibility also support of tourism attraction of the city. Creation inclusive design in the urban space support to improve the quality and sustainability of municipal services. Inclusive design ensure involving citizens to the city life.